Pediatric Aphakic Glaucoma - Ihsan Ali, Zia Muhammad John Grigg, Ikramullah (Pakistan Journal of Ophthalmology, 2019)
Purpose: To find the frequency and pathogenesis of post-operative aphakic glaucoma in children operated for congenital cataract at Mardan Medical Complex, Mardan, Pakistan. Study Design: Retrospective Cohort study. Place and Duration of Study: Mardan Medical Complex, Mardan between January 2001 and December 2014. Material and Methods: All cases were operated for congenital cataracts between the ages of 2 months to 30 months were included in the study. Babies having congenital cataracts with increased intraocular pressure (IOP), those showing signs of congenital glaucoma and those having congenital cataracts with specific syndromes were not included in the study. Results: We reviewed the records of 110 patients who had bilateral lens aspiration for congenital cataracts. We found 7 patients (12 eyes) who developed increased intra-ocular pressure (IOP) after bilateral lens matter aspiration for congenital cataracts. Four patients (three males one female), developed early onset pupil block glaucoma, (2 bilateral and 2 unilateral) while in 3 female patients the onset of glaucoma was delayed for several months to years and was of the open angle type in both the eyes. Poor compliance with follow up, poor pupillary dilatation, prolonged surgical time, severe inflammation and residual lens matter are some of the risk factors for early onset pupillary block aphakic glaucoma in pediatric age group. Conclusions: Pediatric aphakic glaucoma is a significant complication of congenital cataract surgery which requires continuous followup of the patients. Key Words: Pediatric aphakic glaucoma, Congenital cataract, Aphakic open angle glaucoma, Pupil block, Primary posterior capsulotomy,